Role and future applications of extracellular vesicles in HIV-1 pathogenesis. (April 2015) - Hubert, Audrey; Barbeau, Benoit; Subra, Caroline; Bissonnette, Luc; Gilbert, Caroline
ABSTRACT : Extracellular vesicles (EVs) are released naturally in vivo and in vitro from cells and tissues into biological fluids such as plasma, urine, saliva and amniotic fluid, and into culture medium. EV may contain proteins, lipids, mRNA and miRNA significant of the physiological status or of their cellular origin and affect the functions of neighboring cells. The characterization of EVs present in HIV-1-infected individuals provides insight into pathogenesis, inflammation and disease progression. However, the potential of EVs to become reliable research or diagnostic tools is currently limited by the difficulty of distinguishing apoptotic and plasma membrane EVs, exosomes and virions. In spite of this methodological limitation, EVs are expected to become highly useful tools in biomedicine and uncover a research area expected to lead to innovative R&D.